“Romantic” Image of Childhood in the Work of Jovan Sundečić - Kalezić-Radonjić, Svetlana (Poznańskie Studia Slawistyczne, 2023)
In this paper I analyze one of the first collections of poems for children in the SCBM language, Niz dragocijenoga bisera ili Duhovne i moralne pjesme za djecu by Jovan Sundečić (Zadar 1856, Cetinje 1865). Although many have stated that it is one of the first original publications intended for children and young readers of the South Slavic area, there has been no detailed analysis of it until now. In the introductory part of the paper, I will look at the circumstances which led to creation of literature for children and young people, in the central part, through the analysis of Sundečić’s book, I will show why Romanticism in children’s literature inevitably intertwined with Enlightenment, and I will try to illuminate the socio-historical circumstances that led to the reprint. In the conclusion, I make an evaluation of the book from the viewpoint of Romanticism, as the period in which it was created, as well as the contemporary moment, which tends to mark the timeless literary qualities.